Holistic Character Formation Through Adab-Based Educational Design In Indonesian Islamic Boarding Schools - Bambang Wahrudin; Imam Fuadi; Kojin Mashudi (International Journal of Education Management and Religion, 2025)
The damage to the character of adolescents and students in educational institutions has been felt by many perpetrators and observers of education. This condition requires educational institutions to be serious in forming character, one of which is by organizing adab education. Educational institutions that are considered successful in organizing the management of adab education so that they are able to produce a generation with Islamic character, one of which is Islamic boarding schools. This research reveals the phenomenon of adab education management carried out by PP Darul falah Ponorogo which is one of the institutions with success in character education. The results obtained from this study that the management design of adab education in forming Islamic akrkater implemented at PP Darul Falah Ponorogo include; 1) Planning Traditional Education Management, 2) Mapping the Potential, Talents and Interests of Students, 3) Distribution of Main Tasks and Functions, 4) Making Commitments, 5) Determining Programs and Activities, 6) Formulating Monitoring and Evaluation Models. This design has proven to be successful in shaping the Islamic character of students at PP Darul Falah Ponorogo.